Brain development in ADHD. (February 2015) - Friedman, Lisa A; Rapoport, Judith L
Highlights: Anatomic brain MRIs show anomalies in ADHD, especially in nonremitting patients. Deviant brain developmental trajectories are present in ADHD. Stimulant drug treatment 'normalizes' anatomic and functional measures in ADHD. Neuroimaging is a useful intermediate phenotype for familial/genetic impact in ADHD. Abstract : Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder with underlying brain anatomical and functional measures, as well as familial/genetic factors that are major foci of neuropsychiatric research. Advances in imaging technology have shown structural and functional brain differences between individuals with and without ADHD. Longitudinal studies have enabled the elucidation of differences in developmental course. Studies comparing persisting and remitting cases of ADHD are particularly promising. Therapeutic doses of psychostimulants normalize many measures of brain anatomy and function.